(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
There is an increase in the cases of erectile dysfunction and the remedies so far are not without side effects thus, this study is aimed at investigating the influence of aqueous crude extract of tiger nut (Cyperus esculentus) on some important biochemical indices involved in penile erection in male Wistar albino rats. Twenty-four adult male Wistar rats were divided into four (4) groups of five (5) rats each. One group (control) received distilled water, the other groups received 250, 500 and 1000 mg/kg of C. esculentus aqueous crude extract respectively for fourteen (14) days. Administration was done orally (once daily) with the aid of a gavage. At the end of the experimental period, blood samples were collected through the abdominal aorta into plain sample containers to obtain serum for biochemical analysis. Nitric oxide (NO), sex hormones, fasting blood glucose, lipid profile, serum liver enzymes (ALT and AST) and haematological parameters were assayed using standard methods. Body weight of the animals and organs (testis and kidney) were also monitored at intervals of seven (7) days after basal value had been taken. The results showed significant (p<0.05) reduction in body weight in the second week at 500 mg/kg in relation to basal values. Significant decrease and increase were observed in the weight of kidney and testes respectively in some of the groups when compared with the control group. Significant increase was observed in NO levels in the testes. Follicle stimulating hormone and testosterone increased in a non-dose dependent manner. With the exception...